Critical historical archaeology - Leone, Mark P. (Walnut Creek, California Left Coast Press, 2010)
How can we use the past to make sense of the issues and problems that concern us in the present? Mark Leone, the leading critical theorist in historical archaeology, urges archaeologists to view their discipline as an activist pursuit. This volume is partly his autobiographical reflection on a thirty five year career, part a collection of Leone's classic writings on Annapolis, Williamsburg, Shakertown, St. Mary's, and other key sites, and part a synthesis of his current thinking on how historical archaeology can engage the cultural and political issues of our time. Critical Historical Archaeology is an important summary of the work and thinking of one of our most thoughtful, influential archaeologists. -- Book Jacket.
Colonial Williamsburg, Virginia -- Shakertown at Pleasant Hill, Kentucky -- Catholic and Protestant Relations in Maryland -- Establishing Site Significance -- The Virtues of Various Archaeological Theories -- The William Paca Garden as Ideology, not Taste -- Technologies of the Self -- Ideology at Work as Religion -- Mormon Fences -- Mental Instability -- Subversive Genealogy -- Public Tours -- Althusser at Work -- Exhibits -- The Ending.
Includes bibliographical references and index.
ASP-1373 donated by Michelle Eusebio Ph.d.
Keywords: Archaeology and history; Excavations (Archaeology)